Man, analogy of God: Universal Dialectics and Creation in John Scottus Eriugena (Doctor Virtualis, 2023)
In the thought of John Scottus Eriugena, an analogical relationship may be found between God and human nature. Last of the great Neo-Platonists, he proposes a philosophical system distinguished by a universal movement divided into three moments: creation, development and return. They are identified respectively with thought, speech and understanding; all three show the analogy between the creator and his creature. In the beginning, the primordial causes of all things consist in definitions, conceived by God through the human intellect. In the operation that develops them into their effects, these causes are pronounced in and by the Verb according to the rules of dialectics, to be received and understood by Man. Finally, the return to the original unity coincides with the understanding of the universe, through a study of scripture and nature, instruments necessary to reconstitute human nature shattered by the original sin and allow its deification. The study of the analogical relationships that constantly arise in these three universal stages allows us to show the originality of Eriugenian philosophy and its ability to rework philosophical concepts from the late antique tradition in a novel way.
Keywords: John Scottus Eriugena; Neoplatonism; Anthropology; Dialectics; Exegesis; Deification